2011
DOI: 10.3109/14992027.2011.599868
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring auditory training to patient needs with single and multiple talkers: Transfer-appropriate gains on a four-choice discrimination test

Abstract: OBJECTIVE Our long-term objective is to develop an auditory training program that will enhance speech recognition in those situations where patients most want improvement. As a first step, the current investigation trained participants using either a single talker or multiple talkers to determine if auditory training leads to transfer-appropriate gains. DESIGN The experiment implemented a 2 × 2 × 2 mixed design, with training condition as a between-participants variable and testing interval and test version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 30 publications
(32 reference statements)
3
45
0
Order By: Relevance
“…MSB = multi-speaker babble, SNHL = sensorineural hearing loss; SNR = signal to noise ratio, SRT = speech reception threshold, RAU = rationalised arcsine unit [49]; Adaptive spondee words in babble test [50]; Adaptive 12-choice spondee words with multiple jammers test [51]; AzBio sentences [52]; BKB = Bamford-Kowal-Bench sentence lists [53]; Build-a-sentence test [54]; CID Everyday Sentences = Central Institute for the Deaf everyday sentences [55]; CID W22 = Central Institute for the Deaf word lists [56]; CNC = consonant-vowel nucleus-consonant monosyllables [57]; CNC words [58]; Consonant recognition [59]; CSOA = Communication Scale for Older Adults [60]; CST-A = Connected Speech [audio] test [61]; CST-AV = Connected Speech [audio-visual] test [61]; CUNY = City University of New York sentences [62]; Everyday sounds localization test [63]; IEEE Sentences [64] Four-choice discrimination test [46]; GBI = Glasgow benefit inventory [65]; HHIA = Hearing handicap inventory for adults [66]; HHIE = Hearing handicap inventory for the elderly [67]; HINT = Hearing in noise test [68]; Iowa consonant test [69]; LACE = Listening and Communication Enhancement, [39]; Listening span test [11]; NST = Nonsense syllable test [70]; QuickSIN [70]; R-SPIN = Revised speech perception noise test [71]; SPATS = [72]; SPIN = Speech perception in noise test [73]; SSQ = Speech, Spatial and Qualities of Hearing Scale [74]; Stroop Color Word test [75]; TIMIT sentences [76]; VAST = Verb and sentence test [77]; Vowel recognition [78].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MSB = multi-speaker babble, SNHL = sensorineural hearing loss; SNR = signal to noise ratio, SRT = speech reception threshold, RAU = rationalised arcsine unit [49]; Adaptive spondee words in babble test [50]; Adaptive 12-choice spondee words with multiple jammers test [51]; AzBio sentences [52]; BKB = Bamford-Kowal-Bench sentence lists [53]; Build-a-sentence test [54]; CID Everyday Sentences = Central Institute for the Deaf everyday sentences [55]; CID W22 = Central Institute for the Deaf word lists [56]; CNC = consonant-vowel nucleus-consonant monosyllables [57]; CNC words [58]; Consonant recognition [59]; CSOA = Communication Scale for Older Adults [60]; CST-A = Connected Speech [audio] test [61]; CST-AV = Connected Speech [audio-visual] test [61]; CUNY = City University of New York sentences [62]; Everyday sounds localization test [63]; IEEE Sentences [64] Four-choice discrimination test [46]; GBI = Glasgow benefit inventory [65]; HHIA = Hearing handicap inventory for adults [66]; HHIE = Hearing handicap inventory for the elderly [67]; HINT = Hearing in noise test [68]; Iowa consonant test [69]; LACE = Listening and Communication Enhancement, [39]; Listening span test [11]; NST = Nonsense syllable test [70]; QuickSIN [70]; R-SPIN = Revised speech perception noise test [71]; SPATS = [72]; SPIN = Speech perception in noise test [73]; SSQ = Speech, Spatial and Qualities of Hearing Scale [74]; Stroop Color Word test [75]; TIMIT sentences [76]; VAST = Verb and sentence test [77]; Vowel recognition [78].…”
Section: Resultsmentioning
confidence: 99%
“…Participant samples included people with hearing loss without hearing aids or cochlear implants [37], [40], [42], new [38] and existing hearing aid users [38], [41], [46], experienced cochlear implant users [36, 41 43–45, 47], and bimodal (cochlear implant plus hearing aid) users [48]. However, samples were not always consistent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training-induced changes in young adults may be more robust and resistant to change than those in older adults. In fact, two studies that trained perception of time-compressed speech found that younger but not older adults retained training benefits (Barcroft et al, 2011; Peelle & Wingfield, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…One of the authors’ (M.S.) other experiments concerns training the use of newly-fitted hearing aids, (Barcroft et al, in press). When asked about the effectiveness of training, a participant in that study responded that he had not realized how bad his hearing was prior to training and use of the hearing aid.…”
Section: Discussionmentioning
confidence: 99%